Dimensões epidemiológicas da saúde bucal da população rural de Itaúna, Minas Gerais, 2002 - Mauro Henrique Nogueira Guimaraes de Abreu (2004)
In order to evaluate socioeconomic determinants on oral health conditions in rural populations, a quantitative and qualitative epidemiological study were designed, in rural area in Itaúna-MG, in 2002. A cross-sectional quantitative study was conducted with 476 scholarships and qualitative study was developed with 29 mothers. Social and economic indicators, measured by income, level of education, ocupation and access to treated water, indicated that majority of population lives in deprived conditions. DMFT and dmft, oral health measures, were equal to 0,94 (+-1,55) and 4,00 (+-3,46, indicating that health promotion politics are necessary for this group. Logistic regression have showed that 7 to 8-year old children with better socioeconomic status, have had higher odds for dental caries. Content analysis has showed that social representations of health-illness process were related to food intanke and medical service utilization. Oral health process was associated to oral hygiene and diet rules. dental caries were considered an unavoidable experience but tooth loss was not. In spite of objective material conditions in rural areas have not made possible favorable oral health practices; mothers were considered responsible for children oral health. This situation caused bad feelings to these womem and, as consequence, bad quality of life.